1995
DOI: 10.1148/radiology.196.1.7784584
|View full text |Cite
|
Sign up to set email alerts
|

Glenoid labrum: MR imaging with histologic correlation.

Abstract: There are several causes of altered intralabral signal intensity. A transitional fibrocartilaginous zone correlates with sublabral increased signal intensity. Intraarticular administration of gadolinium improves evaluation of the glenoid labrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 0 publications
0
28
0
2
Order By: Relevance
“…Half of these normal labral segments had abnormal morphology or signal characteristics on arthrographic MR images. Labral signal variability may become more prominent in middle-aged patients [25,26] and in patients with chronic injuries [25,27]. The labrum can be variable in size and shape, and morphological criteria may not be sufficient to distinguish a small, normal labrum from a blunted, deficient labrum.…”
Section: Glenoid Labrummentioning
confidence: 99%
“…Half of these normal labral segments had abnormal morphology or signal characteristics on arthrographic MR images. Labral signal variability may become more prominent in middle-aged patients [25,26] and in patients with chronic injuries [25,27]. The labrum can be variable in size and shape, and morphological criteria may not be sufficient to distinguish a small, normal labrum from a blunted, deficient labrum.…”
Section: Glenoid Labrummentioning
confidence: 99%
“…Im Vergleich zur Literatur [4,9,10,19,22] [14,18,23]. In histo-pathologischen Untersuchungen konnte fibrovaskuläres und synoviales Gewebe nachgewiesen werden, welches in verletzte Areale des Labrums einsprosst [24,25] und sich nach intravenöser KM-Gabe gut abgrenzen lässt (s. Abb. 3).…”
Section: Diskussionunclassified
“…3). Bei der direkten MR-AR kann dieser Effekt durch eine Absorption des intraartikulär eingebrachten Gd-DTPA zwar ebenfalls beobachtet werden, ist hier jedoch nur gering ausgeprägt [24].…”
Section: Diskussionunclassified
“…Intralabral signal abnormalities could result from histologic entities including fibrovascular tissue or mucoid or eosinophilic degeneration [20]. Multiplanar gradient-echo sequences in one study showed linear or globular signal in normal labra, although analysis was possibly confounded because the proposed normal population included asymptomatic healthy subjects without surgical correlation [20].…”
Section: Discussionmentioning
confidence: 99%